Analysis of the Financial Performance Comparison Between Islamic Banks and Conventional Banks Listed on the Indonesia Stock Exchange for the Period 2014 - 2018 - Intan Pramudita Trisela,; Ulfi Pristiana, (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
In Indonesia, there are two types of commercial banks: conventional banks and Islamic banks. This study aims to compare the financial performance of conventional banks with Islamic banks for the period 2014-2018 listed on the Indonesia Stock Exchange (IDX). The parameters used to compare banking financial performance involve financial ratios using the REC (Risk Profile, Earnings, Capital) analysis method, which includes five financial ratios: NPL/NPF, LDR/FDR, ROA, BOPO, and CAR. The population of this study comprises 45 conventional banks and 6 Islamic banks listed on the IDX. The sampling was conducted using purposive sampling, resulting in a sample of 3 Islamic banks represented by Bank Rakyat Indonesia (BRI) Syariah, Bank Negara Indonesia (BNI) Syariah, and Bank Mandiri Syariah, and 3 conventional banks represented by Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), and Bank Mandiri. The data used in this study were obtained from annual financial reports published by each of the banks studied. The data analysis technique used is the Independent Sample t-test. The results of this study indicate that there are significant differences between conventional banks and Islamic banks in terms of NPL, LDR, ROA, BOPO, and CAR ratios. Conventional banks perform better in terms of NPL, ROA, BOPO, and CAR ratios, while Islamic banks perform better in terms of the LDR ratio.